MWH's water treatment : principles and design - Crittenden, John C.; Trussell, R. Rhodes ;Hand, David W. ;Howe, Kerry J. ;George Tchobanoglous (New jersey : John Wiley & Son, Inc., 2012)
"Updating the most comprehensive and complete guide to water treatment planning and design, this edition maintains the book's broad scope and reach, while reaching the working professional with additional worked problems and new treatment approaches. It covers both the principles and theory of water treatment as well as the practical considerations of plant design and distribution. The contents have been updated to cover changes to regulatory requirements, testing methodology, and design approaches, as well as the emergent topics of pharmacological agents in the water supply and treatment strategies"--Provided by publisher.
Contents: Inroduction Physical and chemical quality of water Microbiological quality of water Water quality management strategies Principles of chemical reactions Principles of reactor analysis and mixing Principles of mass transfer Chemical oxidation and reduction Coagulation and flocculation Gravity separation Granular filtration Membrane filtration Disinfection Air stripping and aeration Adsorption Ion exchange Reverse osmosis Advanced oxidation Disinfection/oxidation by-products Removal of selected constituents Residuals management Internal corrosion of water conduits Synthesis of treatment train: case studies from bench to full scale
Includes bibliographical references.
Keywords: WATER -- PURIFICATION